Strategi Perencanaan Manajemen Pariwisata Balkondes Borobudur Di Era New Normal - Dian Marlina Verawati; Andhatu Achsa; Rian Destiningsih (Jurnal Ilmiah Poli Bisnis, 2021)
Magelang Regency has twenty Balkondes interesting to visit. One of them is Balkondes first Balkondes Borobudur in Magelang Borobudur Region. Balkondes Borobudur is one of the Balkondes which has its own uniqueness in buildings with classic nuances and beautiful views. After Covid -19 Pandemic, public trust in activities outside the home, especially for traveling, is still very minimal, it also has an impact on the number of tourists visiting Balkondes Borobudur. For this reason, it is very necessary for tourism management planning to make an appropriate strategy for the continuity of Balkondes Borubodur tourism in this new normal era. The purpose is to provide an overview of the results of the analysis of tourism management planning strategies at Balkondes Borobudur in the new normal era. The research method used descriptive qualitative and survey through 7 Respondents Balkondes manager Borobudur. The results showed that Balkondes Borobudur is in quadrant 3 where Balkondes Borobudr must make strategic changes to improve and find the right solution or strategy for the survival of Balkondes Borobudur.